Эколого-физиологические особенности популяции непарного шелкопряда (Porihetria dispar L.) в Нижнем Приднепровье. Сообщение II. Паразиты и болезни - Колыбин, В.А.; Зелинская, Л.М. (Вестник зоологии, 1971)
Under conditions of the Lower Dnieper area about 20 species of parasitic ami car nivorous insects are found, affectitig Porthetria dispar L. Anastatus dispar R h u s с li is of greatest importance in limiting the number of the pest at an egg stage, Apanteles vitripennis Ha l — at a caterpillar stage, Sarcophagidae — at a pupa stage. In the region under investigation the death of P. dispar L. is established evoked by polyedros and microsporidios. The role of parasites, carnivorous insects and diseases in limiting the quantity is not the same in different micropopulations and changes according to the pest gradation phases.